(untitled) (Global Journal of Medical Research, 2016)
This study aimed to reveal the role and altered immunohistochemical expression of αcatenin in oral squamous cell carcinoma progression in its three histopathological differentiations. Immunohistochemical method was used to stain 81 biopsy taken from 81 patients and 15 control sample from normal oral mucosa. α-catenin was detected with homogenous strong staining in 56.6%, 40%, 15% of well, moderately, poorly differentiated squamous cell carcinomas, respectively with p